The Effects of Railway Investments in a Polycentric City - Ghebreegziabiher Debrezion; Eric Pels; Piet Rietveld (Tinbergen Institute, 2004)
This paper analyses the effect of railway investment on land prices and land use in a polycentric city under various regulatory regimes of land markets. The introduction of a faster mode of transport (train), accessible in discrete locations leads to an extended city size. The stations of the “fast” mode attract dense residential settlements. As a result, the average residential and commercial land rents increase in both the competitive and segmented land market situations, as compared with the “slow” unimodal transport case. When rail investments only serve one particular centre, this leads to the growth of the advantaged centre at the expense of the other centre. Generally speaking, investment in the fast mode results in city growth and increase in rent receipts. However the effect of the investment for individual centres and their corresponding residential areas depends on the underlying land market assumptions and the level of investment. Distorted land markets lead to increases in commercial rents, but this is more than off-set by the decrease in residential land rent.
Keywords: R14; R40; 330; Schienenstrecke; Streckenbau; Verkehrsinvestition; Städtische Flächennutzung; Bodenpreis; Schienenverkehr